Overcoming a spouse passing A study on the coping mechanisms among widows in relation to resiliency. - Doligon, Marcela S., et al.; Esparagoza, Erwin D.; Requitillo, Brian M. (Tacloban City Marcela C. Doligon, 2010)
In this study, the researchers sought to explore the coping mechanisms of widows in relation to resiliency after they have experienced grief and bereavement. The problem that is sought to be solved by the researchers is to evaluate the extent of which resiliency helps to alleviate widows from all the negative effects of losing their spouse. The researchers identified their locale as Tacloban City, and selected 15 respondents making this study a qualitative research. Through the span of the data-gathering procedure, the researchers found out that the data-gathering procedure, the researchers found out that the passing of the husband has both internal and external effects. This leads the researchers to conclude that all aspects of the widow were affected because of the death. In light of this, the widows develop coping strategies which eventually lead to successful coping and a resilient widow. Making this study a qualitative one is the main recommendation of the researchers.
Undergraduate thesis (B.A.S.S. Psychology)--University of the Philippines, Tacloban
Keywords: Social Science